Dr. Ambedkar’s Advocacy for Dalit Rights: A Study of his Struggle for Social, Political, and Economic Justice - Dr. Nilesh Chandrakant Adhav (INTERNATIONAL JOURNAL OF SOCIAL SCIENCE & INTERDISCIPLINARY RESEARCH ISSN: 2277-3630 Impact factor: 8.036, 2025)
This systematic study explores Dr. B.R. Ambedkar’s advocacy for Dalit rights, focusing on his strategic efforts to challenge the caste system and secure social, political, and economic justice for the Dalit community. The paper systematically analyzes Ambedkar’s approach to addressing caste-based discrimination through education, legal reform, political participation, and economic empowerment. Through a review of his writings, speeches, political actions, and the constitutional framework he crafted, the study aims to provide a comprehensive understanding of how Ambedkar’s methods continue to shape Dalit rights discourse today. The research follows a thematic structure, dissecting his methodologies in different areas of advocacy while assessing their long-term impact on Dalit empowerment.